A dual mechanism promotes switching of the Stormorken STIM1 R304W mutant into the activated state - Marc Fahrner (Nature Portfolio, 2018)
Stormorken syndrome is associated with the R304W mutation in STIM1, which is a Calcium sensor in the endoplasmic reticulum. Here authors use FRET and electrophysiology to show that R304W induces STIM1 conformational extension by a dual mechanism resulting in constitutive activation of Ca2+ channels.